Sol-gel synthesis of Li3VO4/C composites as anode materials for lithium-ion batteries - Thauer, Elisa; Zakharova, G. S.; Wegener, Simon; Zhu, Q.; Klingeler, Rüdiger (Journal of alloys and compounds, 2021)
Li3VO4/C composites have been synthesized by a sol-gel method and post-annealing at 650 °C for 1 h in N2 flow using either tartaric acid, malic acid, or glucose as both chelating agents and carbon source. The presence of these organic additives crucially affects morphology and crystallite size of the final product. It is found that the electrochemical properties of Li3VO4/C as anode material for Li-ion batteries (LIBs) are influenced by the morphology, texture and carbon content of the material. When using carboxylic acids as carbon source composites with mesoporous structure and a high surface area are obtained that display an enhanced electrochemical activity. Initially, reversible capacity of about 400 mAh g−1 is obtained. In contrast, Li3VO4/C synthesized with glucose outperforms in terms of cycling stability. It exhibits a discharge capacity of 299 mAh g−1 after 100 cycles corresponding to an excellent capacity retention of 96%. The favorable effect of carbon composites on the electrochemical performance of Li3VO4 is shown.